Cognitive mechanisms influence the relationship between social anxiety and depression among college students. Issue 3 (3rd April 2021) - Kraft, Jacob D.; Grant, DeMond M.; White, Evan J.; Taylor, Danielle L.; Frosio, Kristen E.
Abstract: Objective: Social anxiety and depression are commonly comorbid and cause significant impairment in college students. Past research suggests that both poor attentional control and increased rumination are related to these disorders and independently mediate their relationship. Theory suggests that social anxiety loads working memory, thus decreasing attentional control, which influences rumination and depression. The current study aimed to investigate the potential combined influence of attention control and rumination on social anxiety and depression. Participants: Participants (80) were recruited from a large Midwestern university in September 2017. Methods: Participants completed questionnaires regarding social anxiety, attentional control, rumination, and depression and data were analyzed using bias-corrected bootstrapping analyses. Results: Results demonstrate a significant indirect relationship between social anxiety and depression through attentional control and rumination. Conclusions: Results indicated that college students with social anxiety may be at risk for depression due to decreased attentional control and increased rumination. Clinical implications are discussed.